A Review of the Challenge-Hindrance Stress Model: Recent Advances, Expanded Paradigms, and Recommendations for Future Research - Horan, Kristin A.; Nakahara, Wheeler H.; DiStaso, Michael J.; Jex, Steve M. (Frontiers in Psychology, 2020)
Since its introduction approximately 20 year ago, the Challenge-Hindrance Stress Model (CHM) has been widely accepted both among academic and practitioner audiences. The model posits that workplace stressors can be grouped into two categories. Hindrance stressors will interfere with performance or goals, while challenge stressors contribute to performance opportunities. These two categories of stressors are theorized to exhibit differential relationships with strain, with hindrance stressors being more consistently linked to psychological, physical, or behavioral strain compared to challenge stressors. Despite the popularity of this model, recent evidence suggests that the proposed differential relationship hypothesis has not consistently held true for all types of strain. Thus, a reexamination or modification of this paradigm is clearly warranted. In the present review, we describe existing evidence surrounding the CHM and describe the rationale for a shifting paradigm. We outline recent advances in research using the CHM, such as novel moderators and mediators, the need to explicitly measure challenge and hindrance appraisal and differentiate between hindrance and threat appraisal, the dynamic nature of these appraisals over time, and the recognition that a single stressor could be appraised simultaneously as both a challenge and a hindrance. Finally, we provide recommendations and future research directions for scholars examining stress and stress management through a CHM lens, including recommendations related to study design, the measurement of stressors, the integration of CHM with other models of stress, and interventions for stress management.